Comparação de herbicidas e métodos de aplicação, na cultura do algodoeiro (Gossypium hirsutum L) - Oliveira Begazo, José Carlos Enrique; Sediyama, Tuneo (Revista Ceres, 2025)
The effect of the herbicides Treflan and Diuron alone and the combinations of Treflan + Diuron and Treflan + Linuron were compared with hand weeding and no weeding on cotton at the Experiment Station of the Federal University of Viçosa located at Capinópolis, Minas Gerais. Treflan or Diuron applied alone were not effective, although Treflan gave good control of the grasses. Treflan + Diuron and Treflan + Linuron controlled both grass and broadleaf weeds. The yields of raw cotton fromthese treatments were equal to the yield from hand weeding.